IBN MAS'ŪD'S CONTRIBUTION IN HADITH CRITICISM: Efforts to Preserve the Prophet's Hadith in the Era of Ṣaḥābah - Miladiyah, Faridatul; Muhid, Muhid; Nurita, Andris (Nabawi: Journal of Hadith Studies, 2023)
Al-Idlibī's stated that several ṣaḥābah have criticized hadith, including Ibn Mas'ūd. This seems contrary to the fame of Ibn Mas’ūd as mufassir. So the contribution (criticism of hadith) of Ibn Mas’ūd becomes a necessity to examine how far he preserved the hadith at his time and what method he applied bearing in mind that at that time several other ṣaḥābah also did hadith criticism. The purpose of this research is to fīnd out the contribution of Ibn Mas’ūd in the fīeld of hadith, especially criticism of hadith. This research is closely related to the criticism of hadith at the time of the ṣaḥābah,after the death of the Prophet whichtheycould not ask him directly. This research uses a qualitative-descriptive method, with the type of library research, based on sources from a number of classic books, books, journals which are then collected so that they become valid data. Based on the fīnal results of this research, through the criticism conveyed by Ibn Mas’ūd there are two methods that he applies in criticizing the hadith dukhān: 1) criticism of al-khārijī (sanad) delivered directly to the person who brought the news about dukhān,.2) al-dākhilī (matan) criticism which is applied through the ‘aqli approach (logic) and previous events (historical approach), namely when he was with the Prophet in the war of badr. [Al-Idlibī menyebutkan beberapa sahabat telah melakukan kritik hadis. Di antara para sahabat tersebut adalah Ibn Mas’ūd. Padahal, ia lebih terkenal sebagai mufassir. Dari sini, kontribusi (kritik hadis) Ibn Mas’ūd menjadi keperluan untuk diteliti sejauh mana ia memelihara hadis pada masanya dan bagaimana metode yang ia terapkan mengingat pada saat itu beberapa sahabat lain juga melakukan kritik hadis. Adapun tujuan dari penelitian ini yaitu untuk mengetahui kontribusi Ibn Mas’ūd dalam bidang hadis, khususnya kritik hadis. Penelitian ini berkaitan erat dengan kritik hadis pada masa sahabat, yang mana pasca Nabi wafat mereka tidak bisa bertanya langsung kepada Nabi. Penelitian ini menggunakan metode kualitatif-deskriptif, dengan jenis penelitian kepustakaan (library research), berdasar pada sejumlah kitab klasik, buku, jurnal yang kemudian dikumpulkan supaya menjadi data yang valid. Berdasarkan hasil akhir dari penelitian ini, melalui kritik yang disampaikan oleh Ibn Mas’ūd, terdapat dua metode yang ia terapkan dalam mengkritik riwayat hadis dukhān: 1) kritik al-khārijī (sanad) dilontarkan langsung kepada orang yang membawa kabar tentang dukhān,.2) kritik al-dākhilī (matan) yang diterapkan melalui pendekatan ‘aqli (logika) dan kejadian terdahulu (pendekatan historis), yakni ketika ia bersama Nabi dalam perang badar.]